2020
DOI: 10.22545/2020/00143
|View full text |Cite
|
Sign up to set email alerts
|

Electrome & Cognition Modes in Plants: A Transdisciplinary Approach to the Eco-Sensitiveness of the World

Abstract: Recent studies on plant-environment and plant-human relationships reveal the need to reassess thescales of perception, sensitiveness and cognition of living systems. The complexity of plant's emergingbehaviors in interaction with the environment is supported by the signature of the electrome and theplant sensorium, a strong argument to establish the singularity of the living and weights its consequencesin evolutionary, ecological or socioeconomic terms. This paper highlights the cognitive value of access tothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…C. racemosa and many other plants have predominantly low frequency ranges related to energy expenditure that might increase during operational choice and attention facing external cues [ 9 ]. This phenomenon is remarkable and may have similarities with information processing at the neural scale [ 24 , 25 , 45 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. racemosa and many other plants have predominantly low frequency ranges related to energy expenditure that might increase during operational choice and attention facing external cues [ 9 ]. This phenomenon is remarkable and may have similarities with information processing at the neural scale [ 24 , 25 , 45 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it would be important to further investigate the links between the cyclic and low-frequency activities in C. racemosa and many other plants, our results indicated that, whatever the cognitive value we attribute to the perceptual process involved (such as selective attention), the operating mode was, in the particular case of the dodder: (1) hostselective (operational choice), (2) energy-intensive (in proportion to the frequencies detected), (3) associated with a possible state of attention on transdisciplinary grounds [9], and (4) of a mesological order (Umwelt of plants, a direct link with their singular milieu [44,45]). This is in line with other studies on electrome complexity [26,40,43], including some that demonstrated specific electromic signatures in pathogen-infected plants [28,46], bioelectric patterns of oscillations recorded in loco in Miconia sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, quite often, mixed electrical potential waves are recorded, for instance, as a result of overlapping APs and VPs (among other voltage variations), creating a complex bioelectrical information network in which several electrical signals may be superposed [ 4 ]. As a result, the term “electrome” was coined to designate the totality of ionic currents of any living entity, evoked naturally or spontaneously, recorded by non-polarized Ag/AgCl electrodes [ 11 ], and more recently, the term “plant electrome” was employed to refer to the emergent complexity of bioelectrical activity in plants [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies analyzing plant electrome [ 1 , 13 , 14 , 15 , 16 , 17 ] revealed its potential as a tool for early stress diagnosis in plants since the electrome exhibits specific patterns of responses that function as a classifiable electrical signature by standard time series analysis and machine learning techniques [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%